2016
DOI: 10.1186/s13068-016-0439-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and secretomic insight into lignocellulolytic system of an endophytic bacterium Pantoea ananatis Sd-1

Abstract: BackgroundExploring microorganisms especially bacteria associated with the degradation of lignocellulosic biomass shows great potentials in biofuels production. The rice endophytic bacterium Pantoea ananatis Sd-1 with strong lignocellulose degradation capacity has been reported in our previous study. However, a comprehensive analysis of its corresponding degradative system has not yet been conducted. The aim of this work is to identify and characterize the lignocellulolytic enzymes of the bacterium to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…All analysed P. ananatis strains have several CWDEs, including a putative xylanase, pectin acetylesterase, cellulase and two polygalacturonases (De Maayer et al ., ). The lignocellulose‐degrading strain P. ananatis Sd‐1 has an unusually high number of carbohydrate‐active enzymes among members of the species, including enzymes required for the degradation of cellulose and hemicellulose (Ma et al ., ). Included in its arsenal of CWDEs are 59 glycoside hydrolases, 25 carbohydrate esterases, 10 cellulases and two polysaccharide lyases (Ma et al ., ).…”
Section: New Insights Into the Pathogenicity Of P Ananatismentioning
confidence: 97%
See 3 more Smart Citations
“…All analysed P. ananatis strains have several CWDEs, including a putative xylanase, pectin acetylesterase, cellulase and two polygalacturonases (De Maayer et al ., ). The lignocellulose‐degrading strain P. ananatis Sd‐1 has an unusually high number of carbohydrate‐active enzymes among members of the species, including enzymes required for the degradation of cellulose and hemicellulose (Ma et al ., ). Included in its arsenal of CWDEs are 59 glycoside hydrolases, 25 carbohydrate esterases, 10 cellulases and two polysaccharide lyases (Ma et al ., ).…”
Section: New Insights Into the Pathogenicity Of P Ananatismentioning
confidence: 97%
“…The lignocellulose‐degrading strain P. ananatis Sd‐1 has an unusually high number of carbohydrate‐active enzymes among members of the species, including enzymes required for the degradation of cellulose and hemicellulose (Ma et al ., ). Included in its arsenal of CWDEs are 59 glycoside hydrolases, 25 carbohydrate esterases, 10 cellulases and two polysaccharide lyases (Ma et al ., ). Pantoea ananatis is thus well equipped to degrade the integrity of the plant cell wall and cause disease in its host.…”
Section: New Insights Into the Pathogenicity Of P Ananatismentioning
confidence: 97%
See 2 more Smart Citations
“…Fernandez-Fueyo et al (2016) reported lignin degradation with Pleurotus ostreatus. According to Ma et al (2016), P. ananatis Sd-1 produces ligninolytic relevant enzymes in addition to cellulases and hemicellulases. Pereira et al (2016) studied the catabolic pathway for β-aryl ether subunits of lignin.…”
Section: Ligninmentioning
confidence: 99%